Book Sales and Readership Statistics: Ukrainian Trends 2021 (Global Journal of Human-Social Science, 2021)
The research study explores the phenomenon of consumer book buying behavior in COVID-19 The study focuses on Ukrainian reader s taste We applied a questionnaire and obtained 100 responses How much do people spend on books per month What types of books are they buying What genres are they selecting Consumer insights play main role in a publisher s strategies from acquisitions to pricing and marketing campaigns The results here indicate book buying habits of Ukrainian readers who participated in the survey in Kyiv Bukva bookshop in February 2021
Keywords: ukrainian bookstore «bukva»; readership statistics; consumer behavior; best sellers in books